Circular supply chains in emerging economies – a comparative study of packaging recovery ecosystems in China and Brazil. Issue 23 (2nd December 2019) - Batista, Luciano; Gong, Yu; Pereira, Susana; Jia, Fu; Bittar, Alexandre
Abstract : This paper provides a circular supply chain perspective of packaging recovery ecosystems being implemented by Tetra Pak, a prime global player in the food packaging industry, in two major emerging economies: China and Brazil. The circular supply chain archetype considered in the research allowed a consistent comparative analysis of Tetra Pak's circular supply chains in both countries. Through a case study approach, the research provides theoretical propositions and learning points that are valuable for academics and practitioners interested in the Chinese and Brazilian markets as well as in the supply chains supporting recovery ecosystems in the packaging industry. In particular, the distinct environments in the Chinese and Brazilian markets render Tetra Pak opportunities to design circular supply chains in different ways showing adaptation and learning to local market characteristics. The industrial perspectives from these emerging economies add to the contributions offered in the paper. Overall, the conceptual considerations and practical recommendations presented in the paper provide useful insights for the development of further studies and implementation of industrial practices advocated by the circular economy.